The Role of Osteopontin and Osteopontin Aptamer (OPN-R3) in Fibroblast Activity - Hunter, Cedric (2011)
BACKGROUND: Scarring is believed to be caused by both persistent inflammation and overexuberant fibroblast activation. Osteopontin (OPN) is a cytokine that promotes cell activation. The absence of OPN in vivo reduces dermal scarring. This suggests that OPN is involved in scar formation; however, how OPN exerts these pro-scarring effects is unknown. RNA aptamers are short RNA molecules that bind target proteins with high affinity. The aptamer OPN-R3 (R3) blocks OPN signaling. The role of R3 in preventing dermal fibrosis is unknown. METHODS: Fibroblast migration was analyzed with the use of Boyden Chambers and HEMA-3 staining. Inverted confocal microscopy was used to assess fibroblast focal adhesion length. Adhesion was measured by incubating fluorescently stained fibroblasts on OPN coated 96-well plates. CellTiter 96® AQueous Non-Radioactive Cell Proliferation Assay was utilized to investigate the proliferative activity of fibroblasts. Free floating collagen lattices were utilized to assess fibroblast contractility. RESULTS: Human dermal fibroblasts migrated significantly in response to OPN. OPN did not induce a significant increase in focal adhesion length compared to controls. Adhesion studies demonstrated that OPN increased fibroblast adhesion. Proliferation assays indicate that OPN increased fibroblast growth. OPN increased fibroblast contractility of collagen lattices. The addition of R3 significantly inhibited OPN induced activity. CONCLUSION: OPN is associated with scar and exerts pro-scarring effects by increasing cellular migration, adhesion, proliferation, and contractility of human dermal fibroblasts. R3 prevents OPN mediated activity. OPN may be useful for promoting closure of non-healing wounds and the OPN specific aptamer, R3, may be useful for preventing fibrosis.